2006
DOI: 10.1007/s00383-006-1670-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary peritoneal drainage in necrotising enterocolitis: an 18-year experience

Abstract: Primary peritoneal drainage (PPD) was initially introduced as a method for the pre-operative resuscitation of critically ill infants with complicated necrotising enterocolitis (NEC). Some have recommended it as definitive strategy for a select group of extremely low birth weight babies. The role of laparotomy in neonates who do not respond to initial PPD has also been challenged. With this background, we analysed our experience with the use of PPD in babies with NEC over an 18-year period. We retrospectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
1
9
1
Order By: Relevance
“…Goyal et al [8] reviewed their experience with PD for an extended period and concluded that early laparotomy post-PD has a favorable outcome. In this report, our data suggest a contrary conclusion.…”
Section: Discussionmentioning
confidence: 98%
“…Goyal et al [8] reviewed their experience with PD for an extended period and concluded that early laparotomy post-PD has a favorable outcome. In this report, our data suggest a contrary conclusion.…”
Section: Discussionmentioning
confidence: 98%
“…There have also been multiple studies looking at the outcomes for primary peritoneal drainage compared with laparotomy [14][15][16]. The number of [17] examined survival according to whether the bowel affected by NEC was isolated, multifocal, or panintestinal.…”
Section: Discussionmentioning
confidence: 99%
“…Patients that are treated with primary drainage may improve through the evacuation of enteric contents and occasionally the creation of a fistula (27). In certain cases however, patients may deteriorate after peritoneal drainage, necessitating laparotomy (27). The choice of whether to perform primary peritoneal drainage versus laparotomy as first line treatment has been a topic of much study and debate during the past 20 years (24).…”
Section: Clinical Management Of Necmentioning
confidence: 99%
“…In patients with diffuse intestinal necrosis, previous authors have recommended creating a proximal stoma to allow intestinal decompression, followed by relaparotomy as a means to limit the extent of intestinal resection that is performed. Patients that are treated with primary drainage may improve through the evacuation of enteric contents and occasionally the creation of a fistula (27). In certain cases however, patients may deteriorate after peritoneal drainage, necessitating laparotomy (27).…”
Section: Clinical Management Of Necmentioning
confidence: 99%